Encyclopedia of food and culture. Volume 3, Obesity to Zoroastrianism, index - Katz, Solomon H., 1939-; Weaver, William Woys, 1947- (Detroit : Thomson/Gale, 2003)
Contains over 125 entries that provide information about the essential aspects of food, its history, and its cultural diversity, including articles on people who have been influential in food history. Arranged alphabetically from obesity-to-Zoroastrianism, with maps, illustrations, and sidebars.
Includes bibliographical references and index.
Young Adult
Keywords: Food habits -- Encyclopedias; Food -- Encyclopedias; Eating customs -- Encyclopedias; Food -- Encyclopedias